In Situ Homologous Polymerization of L-Lactide Having a Stereocomplex Crystal - Im, Seung Hyuk; Jung, Youngmee; Kim, Soo Hyun (AMER CHEMICAL SOC, 2018)
Polylactide (PLA) is one of the most commonly used biodegradable polymers for various fields such as biomedical and renewable industries. This material must undergo molding processes to achieve the desired shape in the final manufactured product, which are typically thermal- or solvent-based. Unfortunately, the mechanical and thermal properties of PLA, such as the strength and crystallinity, are inevitably damaged during the molding process due to the slow crystallization rate. To overcome this limitation, a simple, novel, one-pot, self-accelerating method for the in situ self-nucleating (ISN) polymerization of L-lactide is developed. This strategy results in the simultaneous polymerization and self-nucleation of L-lactide crystallites upon addition of a self-nucleating agent. The results show that ISN-PLA experiences an acceleration effect on the crystallization with stereocomplex polylactide (sc-PLA) as the nucleating agent and has enhanced mechanical and thermal properties, despite repetitive thermal processing. The ISN polymerization of L-lactide can save considerable time and cost by using the one-pot process composed of both polymerization and self-nucleation. This study suggests a novel strategy for manufacturing industrial products with high strength and crystallinity based on PLA as a promising biopolymer.
Keywords: CRYSTALLIZATION BEHAVIOR; POLY(VINYLIDENE FLUORIDE); NUCLEATING-AGENTS; POLYLACTIDE STEREOCOMPLEX; POLY(L-LACTIC ACID); POLY(LACTIC ACID); RECRYSTALLIZATION; RESISTANCE; EFFICIENCY; NANOTUBES